Biggest of tinies: natural variation in seed size and mineral distribution in the ancient crop tef [Eragrostis tef (Zucc.) Trotter] - Whisnant, Eric D.; Keith, Christian; Smieska, Louisa; Chia, Ju-Chen; Bekele-Alemu, Abreham; Vatamaniuk, Olena K.; VanBuren, Robert; Ligaba-Osena, Ayalew (Frontiers in Plant Science, 2024)
Tef [Eragrostis tef (Zucc.) Trotter] is the major staple crop for millions of people in Ethiopia and Eritrea and is believed to have been domesticated several thousand years ago. Tef has the smallest grains of all the cereals, which directly impacts its productivity and presents numerous challenges to its cultivation. In this study, the natural variation in seed size of 189 tef and 11 accessions of its wild progenitor Indian lovegrass (Eragrostis pilosa (L.) P. Beauv.), and the mineral distribution of representative accessions were analyzed. The findings revealed significant natural variation in seed size and mineral concentration among both the tef and E. pilosa accessions. We observed a significant variation in seed length, seed width, and seed area among the accessions of both Eragrostis spp. analyzed in this study. Furthermore, significant variation in 1000-grain weight was observed among representative accessions of both species. The observed variation in seed size attributes prompted us to perform comparative genomic analysis to identify seed size regulating genes based on the well-studied and closely related monocot cereal rice [Oryza sativa (L.)]. This enabled us to identify putative tef orthologs that belong to a number of key pathways including ubiquitin-proteasome, G-protein, MAPK, and brassinosteroid (BR)-family genes and showed significant similarity to seed size regulating genes in rice and other cereals. Because tef is known to be more nutrient-dense than other more common cereals such as rice, wheat, and maize, we also studied the mineral concentration of selected accessions using ICP-OES and explored their distribution within the seeds using synchrotron-based X-ray fluorescence microscopy. The findings showed a significant variation